1998
DOI: 10.1021/cm9802200
|View full text |Cite
|
Sign up to set email alerts
|

Ternary and Quaternary Uranium and Thorium Chalcogenides

Abstract: A survey of the structural chemistry of ternary and quaternary uranium (U) and thorium (Th) chalcogenides is presented. Specific attention is paid to the coordination environments of U and Th in a variety of classical and nonclassical structure types. The problems of defining the oxidation state of U from UQ (Q = S, Se, Te) bond lengths and magnetic susceptibility data are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 73 publications
1
56
0
Order By: Relevance
“…Advances have been made concerning the controlled syntheses and the understanding of the physical properties of U 5 þ (5f 1 ) compounds, especially among molecular compounds [1], hydrated inorganic materials [2][3][4], and solid-state oxides [5,6]. However, this is not so for solid-state uranium chalcogenides (chalcogen¼ Q¼ S, Se, or Te) [7][8][9]. Many such compounds have been synthesized by the direct combination of elements or by the use of the reactive flux method [10].…”
Section: Introductionmentioning
confidence: 99%
“…Advances have been made concerning the controlled syntheses and the understanding of the physical properties of U 5 þ (5f 1 ) compounds, especially among molecular compounds [1], hydrated inorganic materials [2][3][4], and solid-state oxides [5,6]. However, this is not so for solid-state uranium chalcogenides (chalcogen¼ Q¼ S, Se, or Te) [7][8][9]. Many such compounds have been synthesized by the direct combination of elements or by the use of the reactive flux method [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ternary and quaternary uranium chalcogenide compounds containing d-metals have been the subject of extensive research [1][2][3][4]. There is considerable interest in compounds that contain dmetals, as interactions between the localized 5f electrons and delectrons can lead to interesting physical properties [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in compounds that contain dmetals, as interactions between the localized 5f electrons and delectrons can lead to interesting physical properties [5][6][7][8][9]. Many of these compounds such as MU 8 Q 17 [10][11][12][13][14][15][16][17][18] and MUQ 3 [3,12,[19][20][21] contain 3d metals, whereas fewer compounds have been characterized that contain 4d metals. Examples of these include: AAgUQ 3 (A¼Rb, Cs, Q¼ S, Se) [22], A 2 Pd 3 UQ 6 [23], Rh 2 U 6 Se 15.555 [24], CsZrUTe 5 [25], MUQ 3 (M¼ Ru, Rh, Pd, Q¼S, Se) [26,27], A 2 Pd 4 U 6 Q 17 (A ¼Rb, Cs, Q¼S, Se) [28], Mo 6 UQ 8 (Q¼S, Se) [29], Ba 3 AgUS 6 [30], and Ba 9 Ag 10 U 4 S 24 [31].…”
Section: Introductionmentioning
confidence: 99%
“…Ternary and quaternary uranium chalcogenide compounds containing d metals have been the subject of extended research owing to possible interactions between the localized 5f electrons and d electrons [1,2]. Although numerous 3d-metal ternary and quaternary uranium chalcogenides have been synthesized [3][4][5][6][7][8][9][10][11] only three compounds have been reported that contain Sc, all of them being ternary sulfides.…”
Section: Introductionmentioning
confidence: 99%